Participatory Approaches - and Guijt, Irene (UNICEF, 2014)
This guide, written by Irene Guijt for UNICEF, looks at the use of participatory approaches in impact evaluation. Using participatory approaches means involving stakeholders, particularly those affected by intervention, in the evaluation process. This includes involvement in the design, data collection, analysis, reporting, and management of the study. Excerpt "By asking the question, ‘Who should be involved, why and how?’ for each step of an impact evaluation, an appropriate and context-specific participatory approach can be developed. Managers of UNICEF evaluations must recognize that being clear about the purpose of participatory approaches in an impact evaluation is an essential first step towards managing expectations and guiding implementation. Is the purpose to ensure that the voices of those whose lives should have been improved by the programme or policy are central to the findings? Is it to ensure a relevant evaluation focus? Is it to hear people’s own versions of change rather than obtain an external evaluator’s set of indicators? Is it to build ownership of the UNICEF programme? These, and other considerations, would lead to different forms of participation by different combinations of stakeholders in the impact evaluation."